Measurement, Instrumentation, and Sensors Handbook : spatial, Mechanical, Thermal, and Radidation Measurement - Webster, John G., ....-; Eren, Halit, 1953- (Londen : CRC Press, 2014)
Edited by one of the most renowned instrumentation experts in the world, this bestselling handbook contains nearly 150 contributors covering all aspects of the design and implementation of instrumentation. It describes the use of instruments and techniques for performing practical measurements in engineering, physics, chemistry, and the life sciences. Organized according to measurement problem, each section addresses the different ways of making a measurement for a given variable. Each chapter will be completed updated and presents basic information, a detailed mathematical treatment, advanced applications, and areas for future studies. Edited by renowned instrumentation experts, this new edition of a bestselling handbook brings together nearly 150 contributors covering all aspects of the design and implementation of instrumentation. It describes the use of instruments and techniques for performing practical measurements in engineering, physics, chemistry, and the life sciences. Organized according to measurement problem, each section addresses the different ways of making a measurement for a given variable. Each chapter is completed updated and presents basic information, a detailed mathematical treatment, advanced applications, evaluative options, and areas for future studies. This volume covers spatial, time, and mechanical measurement. The Second Edition of the bestselling Measurement, Instrumentation, and Sensors Handbook brings together all aspects of the design and implementation of measurement, instrumentation, and sensors. Reflecting the current state of the art, it describes the use of instruments and techniques for performing practical measurements in engineering, physics, chemistry, and the life sciences and discusses processing systems, automatic data acquisition, reduction and analysis, operation characteristics, accuracy, errors, calibrations, and the incorporation of standards for control purposes. Organized according to measurement problem.
Keywords: Elektrotechniek